Forging Ahead: Highlights from the 2023 ASMA Conference - Marshall Magnusen (Journal of Applied Sports Management, 2023)
The 2023 Applied Sport Management Association conference took place in Birmingham, Alabama and saw 200 attendees converge on the city to enjoy sport venues, research, and fellowship. It was hosted by Samford University under the direction of Dr. Patrick Marsh and his incredible students. Several highlights from the most recent conference are included in this article.
Keywords: sport management